Correlation of ventricular septal defect height and outcomes after complete atrioventricular septal defect repair. (11th October 2021) - Fong, Laura S; Youssef, David; Ayer, Julian; Nicholson, Ian A; Winlaw, David S; Orr, Yishay
Abstract: : OBJECTIVES: There are limited data available on the height of the ventricular component of the septal deficiency (VSD) in patients undergoing complete atrioventricular septal defect (CAVSD) repair. VSD height may influence optimal choice of repair strategy with potential consequences for long-term outcomes. We aimed to measure VSD height using 2-dimensional echocardiography and review its association with postoperative outcomes. METHODS: We retrospectively reviewed the preoperative echocardiograms of 45 consecutive patients who underwent CAVSD repair between May 2010 and December 2015 at a single centre. VSD height and left ventricular length on the four-chamber view were measured. Demographic details and early and late outcomes including reoperation and long-term survival were studied. RESULTS: Twenty patients underwent modified single-patch repair and 25 patients underwent double-patch repair of CAVSD. VSD height in the modified single-patch group ranged from 4.2 to 11.7 mm and in the double-patch group ranged from 5.1 to 14.9 mm. Nine patients had a deep 'scoop' with a VSD height of >10 mm, (7 double patch, 2 modified single patch). VSD height did not correlate with a specific Rastelli classification. There was no significant difference in the VSD height ( P = 0.51) or the VSD height-to-left ventricular length ratio ( P = 0.43) between the 2 repair groups. There was no 30-day mortality. Eight patients required reoperation; however, VSD height was not a significant predictor of reoperation (hazard ratio 0.95, 95% confidence interval 0.69–1.33; P = 0.08). CONCLUSIONS: There was no correlation between VSD height and risk of reoperation after CAVSD repair. A deep ventricular scoop is uncommon in CAVSD patients. Abstract : Recent studies [1] have demonstrated no significant difference in long-term outcomes based on the surgical repair technique following repair of complete atrioventricular septal defect (CAVSD).